Are America's Inner Cities Competitive? Evidence From the 2000s. (May 2016) - Hartley, Daniel A.; Kaza, Nikhil; Lester, T. William
In the years since Michael Porter's research about the potential competitiveness of inner cities, there has been growing evidence of a residential resurgence in urban neighborhoods. Yet there is less evidence on the competitiveness of inner cities for employment. The authors document the trends in net employment growth and find that inner cities gained over 1.8 million jobs between 2002 and 2011 at a rate comparable with suburban areas. The authors also find a significant number of inner cities are competitive over this period—increasing their share of metropolitan employment in 144 out of 281 metropolitan statistical areas. Also described is the pattern of job growth within the inner city. The authors find that tracts that grew faster tended to be closer to downtown, with access to transit and adjacent to areas with higher population growth. However, tracts with higher poverty rates experienced less job growth, indicating that barriers still exist in the inner city.